1992
DOI: 10.1002/app.1992.070440515
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of acrylamide initiated with electrogenerated cerium (IV) in the presence of EDTA

Abstract: SYNOPSISPolymerization of acrylamide was carried out with cerium( IV) -EDTA redox initiator system with and without electrolysis. The effect of temperature, time, cerium( IV), and EDTA concentrations on the polymerization yield and molecular weight were studied and compared with electrolytic conditions. At low concentrations of cerium( IV ) the electrolytic method continuously supplying Ce ( IV ) from Ce (111) has an advantage over the nonelectrolytic method for which polymerization did not occur under these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…Therefore the polymerization of acrylamide initiated with Ce(IV)-organic reducing agents such as polyamino, amino and carboxylic acids [17][18][19][20][21][22] requires higher energy, longer time and lower acid concentration than initiated with Ce(IV)-organic reducing agents containing thiol groups. In this study, the polymerization of acrylamide using thioglycolic acid-Ce(IV) or KMnO 4 redox system in acidic aqueous medium was examined at room temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore the polymerization of acrylamide initiated with Ce(IV)-organic reducing agents such as polyamino, amino and carboxylic acids [17][18][19][20][21][22] requires higher energy, longer time and lower acid concentration than initiated with Ce(IV)-organic reducing agents containing thiol groups. In this study, the polymerization of acrylamide using thioglycolic acid-Ce(IV) or KMnO 4 redox system in acidic aqueous medium was examined at room temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…However, this method is quite laborious and time consuming. The Mv values were calculated by using the Mark-Houwink equation [18][19][20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differcontains EDTA as an end group. Tripathy et al ent mechanistic pathways have been suggested found that the polymer contains EDTA as an end by many workers [11][12][13][14][15][16][17] to explain the experimental group. 16,17 They also characterized the mechanism observation concerning redox polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Such mechanisms of the polymerization suggest that the reducing agent reacts with Ethylenediaminetetraacetic acid (EDTA), an exthe ceric ion to form an intermediate complex and cellent chelating agent, 1,2 is added to foodstuffs, subsequently decomposes to the free radicals pharmaceuticals, and high-quality cosmetic prodwhich initiate polymer formation. Sarac et al 11 ucts for the control of unwanted trace metal conused the cerium(IV) -EDTA redox initiator systamination. [1][2][3][4][5] Very good catalysts are made when tem with and without electrolysis to study the EDTA forms a complex with cations, but they canpolymerization of acrylamide.…”
Section: Introductionmentioning
confidence: 99%